Emodin influences pyroptosis-related Caspase 1-GSDMD axis alleviated cerebral ischemia-reperfusion injury in rats - Guofang Zhang; Xiaolin Hu; Jun Qian; Yumei Shi; Zeng Ling; Ping Xu; Zucai Xu; Jun Zhang; Tao Liang (Scientific Reports)
Abstract Cerebrovascular diseases, particularly ischemic stroke, are a leading cause of global disability. Effective management of ischemia-reperfusion injury is crucial in stroke treatment. Emodin, known for its anti-inflammatory and neuroprotective properties, has been shown to protect against ischemia-reperfusion injury by modulating pyroptosis. However, the molecular mechanisms underlying its effects in cerebral ischemia-reperfusion injury are not well understood. This study aims to investigate the neuroprotective mechanisms of Emodin in ischemic stroke. SD rats were randomly assigned to different groups: control, sham, model, and Emodin intervention groups with varying dosages. Cerebral ischemia-reperfusion injury was induced using the middle cerebral artery occlusion (MCAO) method, and Emodin (10 mg/kg, 20 mg/kg, 40 mg/kg) was administered intraperitoneally. Neurological deficits were evaluated using the modified Neurological Severity Score (mNSS), and infarct volume was assessed via TTC staining. Pathomorphological changes were observed using HE staining. Protein expression levels associated with pyroptosis, including NLRP3, Caspase 1, and GSDMD, were analyzed by Western blotting and immunofluorescence. The levels of IL-1β and IL-18 were measured using ELISA (Caspase 1 indicates cleaved Caspase 1, GSDMD indicates the active pro-forms of GSDMD, used throughout). Emodin exhibits significant beneficial effects in improving neurological deficits caused by cerebral ischemia-reperfusion injury. It effectively reduces the ratio of infarct volume, alleviates cytopathic damage, and suppresses the expression of pyroptosis-related proteins, including NLRP3, Caspase 1, Caspase 1, and GSDMD. Furthermore, Emodin decreases the levels of pro-inflammatory cytokines IL-1β and IL-18, thus attenuating the inflammatory response. The expression of pyroptosis-related proteins is upregulated in rats after cerebral ischemia-reperfusion injury. Emodin demonstrates neuroprotective effects against cerebral ischemia-reperfusion injury in rats, potentially by modulating the expression of pyroptosis-related proteins mediated through the Caspase 1-GSDMD axis.